EXAFS, SAXS and Eu3+ luminescence spectroscopy of sol-gel derived siloxane-polyethyleneoxide hybrids - Molina, C.; Ribeiro, SJL; Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Craievich, A. F. (Kluwer Academic Publ, 2000)
Hybrid Eu3+-doped silica-poliethyleneoxide (PEO) nanocomposites with covalent bonds between the inorganic (siloxane) and organic (PEO) phases have been obtained by sol-gel process. These materials are transparent, flexible and present high Eu3+ luminescence output. Their luminescence properties, local environment around europium ions and structure have been investigated as a function of europium content. EXAFS measurements indicate that the increase in Eu-doping induces a decrease in Eu3+ coordination number. An increase in symmetry degree around the metal ion is also observed for increasing Eu3+ concentration, while non radiative decay paths from the D-5(0) excited state become more important. SAXS results suggest the preferential interaction of europium ions with ether-type oxygens of the polymer chains. However, the existence of interactions between the cations and the carbonyl groups from urea bridges located at the siloxane-PEO interface can not be excluded.
Keywords: hybrids; luminescence; SAXS; EXAFS